The Factors Affecting Grade Progress in Language Proficiency of Undergraduate Medical Students - Aivar L. Surji; Hannah K. Surji; Soma Hassan Hussein; Aziza Kavlu (International Journal of Social Sciences & Educational Studies)
Language Proficiency is necessary to communicate and comprehend educational concepts. Consistent language practice and routine is essential to maintain growth; hence, an abundant number of breaks can be a hindrance to reaching proper proficiency. This study aims to analyze students’ progression and perspective regarding factors that affect their growth. The contributors were 19 dentistry freshmen from Tishk International University who had limited English language ability. They were assigned to take a supportive foundation English course alongside their medical courses to support their development. Quantitative and Qualitative methods were used to gather data. SPSS was used to analyze grade progression and the effects of breaks on scores. Interviews were applied to grasp the contributors' experience with language learning and the factors they encountered. The participants’ responses presented that substantial workload and lengthy breaks were the factors that affected their language development. The first pair of SPSS data showed that there was not a significant difference (p-value of .05) between the two sets of quizzes as the break was shorter. However, the SPSS results showed that there was a significant difference (p-value of .001) amid the scores of midterms and finals which had a lengthy break between. Therefore, it was found that breaks, workload, and other factors did result in a decline of scores and pupils’ academic progression.